On the Relevance of the Book “Contemporary Philosophy of Education” by L. Duoblienė - Landsbergienė, Austėja (Acta Paedagogica Vilnensia, 2007)
A review of the book “Contemporary Philosophy of Education” by Lilija Duoblienė